Fluorine‐18 Radiolabelling and Photophysical Characteristics of Multimodal PET–Fluorescence Molecular Probes. Issue 3 (9th November 2020) - Klenner, Mitchell A.; Pascali, Giancarlo; Massi, Massimiliano; Fraser, Benjamin H.
Abstract: Positron emission tomography (PET)–fluorescence imaging is an emerging field of multimodality imaging seeking to attain synergy between the two techniques. The probes employed in PET–fluorescence imaging incorporate both a fluorophore and radioisotope which enable complementary information to be obtained from both imaging techniques via the administration of a single agent. Fluorine‐18 is the most commonly used radioisotope in PET imaging and consequently many novel attempts to radiofluorinate various fluorophores have transpired over the past decade. In this Minireview, the most relevant fluorine‐18 labelled PET–fluorescence probes have been classified into four groups as per the implemented fluorophore: 1) boron‐dipyrromethene (BODIPY) dyes, 2) cyanine dyes, 3) alternative organic fluorophores and 4) organometallics, such as quantum dots (QDs) and rhenium complexes. The biological, radiochemical and photophysical properties of each probe have been systematically compared to aid future endeavours in PET–fluorescence chemistry. Abstract : PET–fluorescence is a form of multimodality imaging which enables complementary information to be acquired from both imaging techniques, following administration of a single diagnostic agent. A comprehensive overview of the fluorine‐18 radiolabelling and photophysical characteristics of each known PET–fluorescence tracer is discussed herein, covering historical and recent advances, as well as commentary on future directions.